The religious authorities' competency to make rules in Malaysia: a preliminary remark on the contested power - Shuaib, Farid Sufian (2018)
In the administration of Islamic law in Malaysia, there are several parties and authorities that could exert their influence and power. The Federal Constitution provides legislative powers to Parliament and State Legislature and executive powers to Cabinet and State Executive Council. However, in matters relating to Islam, the Rulers are the Head of Religion. In addition, the Mufti is given power under state law to issue fatwa. The paper seeks to examine the contestation of power among these authorities in the administration of Islam and Muslims.